2018
DOI: 10.1016/j.jtos.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in clinical characteristics of dry eye disease

Abstract: Please cite this article as: Vehof J, Sillevis Smitt-Kamminga N, Nibourg SA, Hammond CJ, Sex differences in clinical characteristics of dry eye disease, Ocular Surface (2018), doi: 10.1016/ j.jtos.2018.01.001. This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Pleas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 29 publications
4
36
1
2
Order By: Relevance
“…Female participants reported higher OSDI scores at earlier age than men. Although sex-based differences in OSDI scores have been reported previously in ocular surface diseases, 22,23 our results highlighted a sex-specific suscepti-FIGURE 2. Clinical assessments of ocular surface system function according to male (left side) and female (right side) subgroups.…”
Section: Discussionsupporting
confidence: 45%
“…Female participants reported higher OSDI scores at earlier age than men. Although sex-based differences in OSDI scores have been reported previously in ocular surface diseases, 22,23 our results highlighted a sex-specific suscepti-FIGURE 2. Clinical assessments of ocular surface system function according to male (left side) and female (right side) subgroups.…”
Section: Discussionsupporting
confidence: 45%
“…26,27 However, because of our large sample size, the fact that we accounted for confounding effects of significant intersex differences in ocular surface and demographics, along with the strength and consistency observed in our results among all the dry eye questionnaires, argues that there is likely a difference in how pain sensitivity influences dry eye symptom between women and men, but additional work will be needed to better define this difference. If, as our study suggests, greater pain sensitivity is found to be more strongly associated with higher dry eye symptoms in women, it could help explain why Vehof et al 28 found that women had a significantly lower correlation coefficient in the association between signs and symptoms of DED compared with men (r = 0.11 vs. r = 0.33, respectively). Pain sensitivity could potentially be a more significant confounder in the association between signs and symptoms for women compared with men.…”
Section: Discussionmentioning
confidence: 54%
“…Previous reports have suggested higher incidence of symptoms of dry eye disease among female subjects, with significantly higher symptom scores and lower correlation between symptoms and signs as compared to males. 77 , 89 Females are represented in our cohort in >2.5:1 ratio to males suggesting that there may be greater incidence, assuming the population undergoing refractive surgery is split equally between the sexes. The PROWL studies were 20% female in the military cohort and 54% female in the civilian cohort.…”
Section: Discussionmentioning
confidence: 99%